COVID-19 - Why we should monitor fatigue indicators in endurance athletes - Escaleira, R. (2020)
Assuming the progressive resumption of training at the highest level, I come to share with you some of the current concerns transversal to the High Performance Medical Community, which are related to the integration of the risk of exposure to SARS-COV2 in the management of training considering the impact of high volume and intensity training on athletes' immune capacity.